Optimisation of batch culture conditions for cell-envelope-associated proteinase production from lactobacillus delbrueckii subsp. lactis ATCC® 7830™ - Agyei, D.; Potumarthi, R.; Danquah, Michael (Humana Press, Inc., 2012)
Using a combination of conventional sequential techniques, the batch growth conditions for the production of cell-envelope-associated proteinases have for the first time been studied and optimised in Lactobacillus delbrueckii subsp. lactis 313 (ATCC 7830; LDL 313). Concentrations of inoculum (0.1 < X < 10 % vol/vol), agitation speed (0 < S < 200 rpm), varying incubation temperature (30 < T < 50 °C), starting pH (4.5 < pH < 7) and carbon/nitrogen ratio of production medium (0.2 < r < 5) had an individual effect on proteinase yield (p < 0.01). Optimal conditions for proteinase production included an initial pH of 6.0, 45 °C incubation temperature, 2 % (v/v) inoculum size of OD560 = 1, 150 rpm agitation speed, and growth medium carbon/nitrogen ratio of 1.0. Maximum proteinase activity obtained for whole cells was 0.99 U/ml after 8 h of incubation. The variables studied are very relevant due to their significance in improving the productivity of proteinase synthesis from LDL 313, under process and, likely, economic optimum conditions.